(3GdeSJOQc Ydi GdUMjMjfs - (3GdMGce GdfjSGHhQj , eMeO Hf YHO Gddg Hf MeOhjg Hf fYje GdVHj GdWgeGfj GdfjSGHhQj, CHh YHO Gddg, GdMGce, GHf GdHjY,J (B405 (3g` s
(3ChdgG (B:s
(3MOKfG GdMGce CHh YHO Gddg eMeO Hf YHO Gddg Hf eMeO GdMGaX EedGA ai jhe GdCKfjf GdSGHY ef GdeMQe SfI KdGK hJSYjf hKdGKeGFI (B: (3GdMeO ddg GdYRjR GdbgGQ s
(3BNQgG (B:s
(3hjfJgi HBNQ cJGH GdHjhY , Hbhdg (B: (3dFdGjJhge eJhge Cfi CNdjJ cJGH GdHjhY Yf gPg GdcJH BNQ GdeLdO GdKGfi ef GdeSJOc hjJdhg ai GdeLdO GdKGdK cJGH GdLgGO s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI hYdjgG NW GdEeGe eMeO Hf EHQGgje Hf GdhRjQ (B_ (3UGMH GdYhGUe hGdbhGUe SfI (B835(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B238s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO RHGQI GdNGUI HUfYGA (B((3MOjK (B8) s
Keywords: (3GdMOjK h GdeUWdMs